Factors and challenges contributing to antimicrobial resistance in East African pastoral settings and importance of One Health approach - Hassan Abdi Hussein; Shaban Mohamed Abdi; Abdullahi Adan Ahad (CABI, 2023)
Abstract Antimicrobial resistance (AMR) is acknowledged as a One Health dilemma because resistant microbial and genes are swiftly appearing and spreading worldwide across humans, animals and the environment. Livestock owners in East African pastoral regions face significant financial and socio-economic challenges owing to animal diseases that can be particularly severe in remote areas, where communities rely solely on their livestock for subsistence. Unfortunately, providing veterinary services in these regions is challenging because of the inadequate infrastructure and limited resources. Consequently, pastoralists may resort to self-medicating their animals, often using antimicrobials in ways that can contribute to the emergence of AMR. Prolonged use, overuse, or misuse of antimicrobial drugs in both human and animal populations in low-income East African pastoral settings is a significant factor that contributes to the emergence of AMR in these regions. Similarly, a significant factor contributing to the spread of AMR in pastoral regions is the disregard for withdrawal periods by pastoralists, owing to a lack of awareness about AMR. Inadequate sanitation protocols and limited access to uncontaminated water sources are additional factors contributing to the dissemination of AMR pathogens in both animals and humans. This leads to critical public health concerns that hinder effective antimicrobial treatment, reduce animal productivity, and have economic consequences for pastoralists. Addressing the challenges associated with AMR requires a comprehensive, multi-sectoral approach that can facilitate the coordinated surveillance and monitoring of AMR, promote the rational use of antimicrobials, advocate for alternative disease prevention and management strategies, and raise awareness among communities and healthcare professionals in pastoral areas about the emergence of AMR. The challenges and factors contributing to AMR in pastoral settings are complex; however, the One Health approach offers a promising strategy for reducing the risk of AMR. This review aims to present a comprehensive overview of the factors and challenges associated with AMR in pastoral settings, and proposes the adoption of a One Health approach as a solution to this pressing issue. One Health impact statement The review highlights that antimicrobial resistance (AMR) in East African pastoral settings is a significant issue that contributes to the emergence and spread of AMR worldwide. Prolonged use, overuse, or misuse of antimicrobials in human and animal populations is a significant factor in the emergence of AMR in these settings. The challenges and factors contributing to AMR in pastoral settings are intricate and call for a multi-faceted approach that encourages rational use of antimicrobials, promotes alternative prevention and management methods, and enhances awareness among Eastern African pastoral communities. The article highlights the significance of adopting the One Health approach in mitigating the hazards of AMR in these settings.